Pemanfaatan Fly Ash Batu Bara Sebagai Adsorben Logam Berat Ion Pb2+ Yang Terlarut Dalam Air - Fauzan, Ananda; Aman, Aman; Drastinawati, Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Utilization of coal into an energy source, resulting in another effectare pollution, such as fly ash generated from burning coal. For that, we need an alternative to overcome this problemis by using fly ash as an adsorbent to adsorb heavy metals lead (Pb 2+) are dissolved in water through adsorption process. This study aimed to calculate the amount of adsorbate (Pb 2+)are adsorbed by the fly ash with mevariasikan adsorbate concentration (Pb 2+) and stirring speed to determine the equilibrium models. The use of fly ash adsorption of 1 g, the sample solution (Pb 2+) on the variation of the concentration of 3, 7, 11 mg/l and variation of stirring speed of 100 rpm and 130 rpm. Solution (Pb 2+) have been obtained and analyzed using AAS, diketahi that the higher the stirring speed jerap capacity fly ash adsorbent (Qe) so that the smaller the amount of adsorbate (Pb) are adsorbed on the wane. In the stirring speed of 100rpm and 130 rpm Qe value is 0.585 mg/g and 0.55 mg/g. Mechanisms of Pb adsorption by fly ash is dominated by the Freundlich isotherm models that represent physical adsorption,where Pb adsorbed by the active site of the fly ash with the influence of the van der walls.Keyword :Fly ash, Adsorbate (Pb 2+)